Ultrasound-Assisted, BF3·OEt2-Promoted, Multicomponent Synthesis of Chromene-Based Podophyllotoxin Analogues - Santos, Fernanda A.; Laurentiz, Rosangela S. (Synlett, 2024)
A novel method was developed to synthesise chromene-lactone analogues of podophyllotoxin using an ultrasound-assisted multicomponent reaction (MCR). The MCR involved tetronic acid, phenols, and aromatic aldehydes and was promoted by BF3·OEt2, resulting in the production of ten derivatives with different substituents on the aromatic rings in yields ranging from 32% to 93%. These compounds are of interest due to their reported activity against tumour cells. Their ease of synthesis through the MCR may allow for more in-depth studies on anticancer activity, as well as investigations of other biological targets. The synthesised derivatives contain important pharmacophoric groups for potential applications in medicinal chemistry.
Keywords: tetronic acid; multicomponent reactions; chromenes; lactones; heterocyclic compounds